Painted pots: the relationship of forms through surface, textural and color interaction - Ortiz, Michael Raymond, author; Kendry, Kenneth A., advisor; Twarogowski, Leroy A., committee member (Colorado State University. Libraries, 1978)
I wish to show in my work, that it is possible to combine the qualities of painting and sculpture into ceramic form. This involves the integration of the surface and form in such a way as to enhance one another. I see ceramic colors, textures, and surface qualities as coming from and flowing with the form; not just as surface decoration, but as a truly integral part of the piece. The forms tell me what direction the surfaces must take on, and what moods the piece should convey. The application of the surfaces reflect abstract painting qualities, utilizing ceramic materials rather than paint. In this way I can get not only color changes, but also textural changes. The surfaces can go from dry and rough to hard shiny glazed areas. The glazes run from opaque mattes to bright transparent glosses. Some edges bleed in to one another, some butt together in hard-edged lines. I want to show contrast plays between light and dark, soft and harsh, smooth and rough. Movement through and around pieces is important to me. Painted surfaces can flow over rims, continue inside the piece, and flow right back over the rim to somewhere else. The lines created by the edges of the painted areas and those painted directly as lines, continue this visual flow through and around the forms. I want to convey contrasting emotional feelings in my work; feelings of visual tension or harmony, stability or instability, and massive or linear qualities. Some of my forms are calm, others are more active, but I feel that they all relate in the way that different emotional moods can flow from one individual. In this way, I arrive at surfaces that are a much more integral part of the ceramics form, than just an inside glaze and an outside glaze. The clay itself, as a plastic material, is important to me. I show how it cracks, tears and stretches. I gouge into it, incise lines, embed other materials into the surface and poke holes into it. Some of my forms show soft loose qualities which tell of the condition of the clay when I built the form. Others appear more rigid when the clay I am using is in a dryer state. Clay is a direct and spontaneous media. I handle it as such in constructing the forms and applying the surfaces. I want my forms to convey the nature of the materials that they are made of. At this point, I am interested in clay forms as vessels. But I feel that a vessel can be more than just a pot. It can be an object of sculptural and painted beauty, which can reflect the spontaneity and directness of clay itself. My forms read as pots, but they function more visually, than as utilitarian vessels.
Zip file contains 24 slides of artist's works.
Keywords: Pottery craft